2009
DOI: 10.1002/ardp.200800216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pp60c‐Src Tyrosine Kinase Inhibitory Activities of Novel Indole‐3‐Imine and Amine Derivatives Substituted at N1 and C5

Abstract: A series of novel 1,3,5-trisubstituted indole derivatives, namely, N-benzyl 5-phenyl indole-3-imine, N-benzyl-5-(p-fluorophenyl)indole-3-imine and their corresponding amine congeners, were designed and synthesized as pp60(c-Src) tyrosine kinase inhibitors, and their inhibitory activities toward pp60(c-Src) tyrosine kinase were evaluated by in-vitro kinase assay. Pre-screening at two doses of compounds against kinase target revealed that, except for the N-benzyl-5-phenyl indole imine derivatives 7a-7d, all indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In our very recent studies, the tyrosine kinase activity and antioxidant capacity of N1 and C5 substituted indole-3-imine and their amine congeners were reported [27,28]. It was shown that amine derivatives from the series 1-(1-benzyl-5-phenyl-1H-indole-3-yl)-N-(4-fluorobenzyl)methanamine hydrochloride, 1-(1-benzyl-5-( p -fluoro)phenyl-1H-indole-3-yl)-N-benzyl methanamine hydrochloride, 1-(1-benzyl-5-( p -fluoro)phenyl-1H-indole-3-yl)-N-(4-chorobenzyl)methanamine hydrochloride and 1-(1-benzyl-5-( p -fluoro)phenyl-1H-indole-3-yl)-N-(4-fluorobenzyl)methanamine hydrochloride had potent inhibition against tyrosine kinase and that they had also slight inhibition against both SOD and LP.…”
Section: Resultsmentioning
confidence: 99%
“…In our very recent studies, the tyrosine kinase activity and antioxidant capacity of N1 and C5 substituted indole-3-imine and their amine congeners were reported [27,28]. It was shown that amine derivatives from the series 1-(1-benzyl-5-phenyl-1H-indole-3-yl)-N-(4-fluorobenzyl)methanamine hydrochloride, 1-(1-benzyl-5-( p -fluoro)phenyl-1H-indole-3-yl)-N-benzyl methanamine hydrochloride, 1-(1-benzyl-5-( p -fluoro)phenyl-1H-indole-3-yl)-N-(4-chorobenzyl)methanamine hydrochloride and 1-(1-benzyl-5-( p -fluoro)phenyl-1H-indole-3-yl)-N-(4-fluorobenzyl)methanamine hydrochloride had potent inhibition against tyrosine kinase and that they had also slight inhibition against both SOD and LP.…”
Section: Resultsmentioning
confidence: 99%